Studi Penerapan Cap String dalam Mengatasi Liquid Loading pada Sumur Gas "X" Lapangan "Y" - Arthur Cesar Bida; Kukuh Jalu Waskita (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Reservoir pressure depletion in gas wells that have been producing for a long period frequently leads to liquid loading, which is the accumulation of liquids at the bottom of the wellbore that restricts gas flow to the surface. This study aims to analyze the factors for selecting candidate wells for cap string installation and to compare production performance before and after its implementation in Well "X" of Field "Y". The evaluation was conducted by analyzing bottom hole pressure (BHP), wellhead pressure (WHP), gas flow rate, liquid production rate, water cut, as well as tubing configuration and perforation intervals. Prior to cap string installation, Well "X" experienced a decline in WHP to below 400 psi, while the gas production rate decreased to nearly zero due to severe liquid accumulation. Following cap string installation, the gas production rate increased to 2.0–3.5 MMscfd, and WHP became more stable within the range of 300–400 psi. The results demonstrate that the cap string effectively increased gas flow velocity, enabling the accumulated liquids to be lifted to the surface and thereby improving overall well performance.